Pengaruh Atraksi, Aksesibilitas, Amenitas, dan Ansilari Pariwisata Halal Terhadap Kepuasan Wisatawan Berkunjung ke DKI Jakarta - Mahda Fikiya (2021)
This study aims to describe the effect of attractions, accessibility, amenities, and ancillary of halal tourism on the satisfaction of tourists visiting DKI Jakarta. This research uses descriptive quantitative with multiple linear regression methods. The population in this study were tourists visiting DKI Jakarta, with a total sample of 100 people who were selected using non-probability sampling techniques. This study uses primary data by collecting questionnaire data via google form, data analysis is carried out using IBM SPSS version 25. The hypothesis of this study is to be able to show a positive and significant effect of attractions, accessibility, amenities, and ancillary of halal tourism on the tourist satisfaction visiting DKI Jakarta.